Cost-effectiveness Analysis of Abdominal-based Autogenous Tissue and Tissue-expander Implant following Mastectomy. Issue 10 (October 2020) - Thoma, Achilles; Avram, Ronen; Dal Cin, Arianna; Murphy, Jessica; Duku, Eric; Xie, Feng
Abstract : Background: Patients who had undergone both autologous abdominal tissue (AAT) and tissue expander and implant (TE/I) breast reconstruction reported satisfaction with their reconstruction. While aesthetics and quality of life are important, the cost associated with these procedures must also be considered when choosing one method over the other. The objective of this study was to determine whether AAT-based breast reconstruction is cost-effective compared with 2-stage TE/I reconstruction at a 12-month follow-up. Methods: Thirty-five patients consented and complied to participate in the study with a follow-up of 12 months. The effectiveness of both AAT and TE/I was measured using the Health Utilities Index Mark 3 (HUI-3). From the HUI-3 results, quality-adjusted life years were calculated for each reconstructive approach. Direct healthcare and productivity costs were captured from surgeon billing codes, patient files, and patient diaries. The perspectives of both the Ministry of Health and of society were considered. Results: From the perspectives of both the Ministry of Health and of society, AAT was less effective and more costly when compared with TE/I. Conclusions: In this economic evaluation, TE/I dominated AAT, in that TE/I was more effective and less costly as compared with AAT from the perspectives of both the Ministry of Health and of society at 12 months of follow-up. This conclusion should be interpreted with caution due to a small sample size, the short timespan of the study, and the nonrandomized study design.